Identification of endoparasitic and ectoparasitic agents in rodents found in university colleges - Tijjani, Mustapha (2019)
The objectives of this study were to determine species of rodents and identify endo and ectoparasites of the rodents from four selected student’s Colleges in Universiti Putra Malaysia (UPM). Rodents were captured using a wire live trapped, humanely euthanised and identified using a key for morphological identification of rodents. Ectoparasites were collected by combing the fur of the rodents on white plain sheet paper. The ectoparasites were washed and mounted with Hoyer’s media on a glass slide for identification. After dissection of the rodents, the blood, tissues, and stool samples were collected and analysed based on standard parasitological laboratory procedures. A total of 89 wild rats that comprised of three species, Rattus rattus diardii, Rattus norvegicus, and Rattus tiomanicus were identified. A total of twelve species (Hymenolepis nana, Hymenolepis diminuta, Aspiculuris tetraptera, Syphacia spp., Strongyloides ratti, Trichuris spp., Heterakis spumosa, Nippostrongylus brassielensis, Giardia spp., Entamoeba histolytica/Entamoeba dispar, Cryptosporidium spp. and Moniliformis moniliformis) of intestinal parasites were identified from the captured rodents. The study reveals that 18.7 % of the rodent examined has at least one species intestinal parasites. Forty-three percent of the rodents were found to be infested with ectoparasites. The ectoparasites species identified include: Laelaps echidnina, Laelaps nuttalli, Ornithonyssus bacoti, Ixodes granulatus, Haemaphysalis spp., Polyplax spinulosa, Hoplopleura pacifica and Xenopsylla cheopis. Trypanosoma spp. was the only blood parasite identified in the present study with low prevalence rate (3.3%). Furthermore, histopathological examination of the tissue sections of brain, liver, lungs, and muscles reveals the presence of parasites that include: Taenia taeniaeformis Strobilocerci (in the liver), Toxoplasma gondii (in the brain), Angiostrongylus cantonensis (in the lungs), Sarcocystis spp. (in the muscle) and Capillaria hepatica (in the liver). The finding of this study showed that wild rats captured from the study area are infected with different parasites of zoonotic importance. This suggests a potential risk of rodent-borne zoonotic disease transmission to humans. Awareness of prevention and control of rodent-borne diseases should also be introduced to educate the students on the importance of zoonotic diseases associated with rodents.